EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN SIDOTOPO I/ 48 - Taufiq, Moh. (Prodi PGMI STIT Sunan Giri Bima, 2023)
This research is quantitative field research with an experimental approach, namely research used to find the effect of treatment on others under controlled conditions. This research aims to measure both classes between classes that were treated and those that were not treated, in this case the researcher used the experimental approach method